A Systematic Review of Pranayama Yoga as a Complementary Therapy in COPD Patients - Yusniar, Firda; Dunggio, Abd. Rivai S.; Suharyono, Suharyono; Pratiwi, Dian (International Journal of Psychosocial Rehabilitation, 2020)
Yoga is one of the top ten complementary and alternative healthcare approaches practiced in the United States, it also gaining popularity in Asia. Pulmonary rehabilitation programs include exercise training, such as yoga, designed to increased the physical and psychological condition in COPD patients. The purpose of this systematic review was to show the effectiveness of yoga as a complementary therapy to COPD patients. Three databases were used to search for the keywords “Yoga Pranayama” AND “Yoga Breathing Exercises*” AND “COPD OR Chronic Lung Disease OR Lung Disease”. This obtained 65 articles, consisting of 21 articles from Scopus, five from PubMed and 39 from ScienceDirect. Fifteen studies were included with inclusion criteria: patient diagnosed with COPD who has symptoms such as dyspnue and decreased activity, aged 18-60 years. Interventions given during the treatment period ranged from two weeks until six months and a frequency of between three or six times every week. Each session reached 10 to 90 minutes. All research was focused on evaluating the impact of pranayama yoga separately or in combination with another type of yoga (dirga svasam, nadhi suddhi asana, kapalabhati, tele-yoga, laughter yoga), or other intervention, such as tai chi, calisthenics, education and, usual care only. On average, studies found yoga pranayama was significantly more effective for six weeks. This systematic review concludes that pranayama yoga is able to be accepted as a complementary therapy for COPD patients because it could improve lung function.